The study of biochemical properties of legume flour (peas, soybeans), physical and baking indicators of the dough from mixtures with wheat flour - E. N. Shabolkina; N. V. Anisimkina; O. А. Maistrenko (Зерновое хозяйство России, 2022)
High protein content, simplicity and time of cooking are two main advantages with which legumes have gained popularity among the population, however, this culture is used not only in its pure form, but also in the form of additives for baking. Adding pea and soybean flour to composite mixtures affects the behavior of the dough, requires corrections in the baking process, and all these issues can be resolved by farinographic analysis. The purpose of the current study was to determine the biochemical parameters of whole-meal pea and soybean flour, to study the rheological properties of the dough of composite mixtures with grain legume flour and to evaluate the efficiency of mixing pea and soybean flour with premium wheat flour according to the results of baking assessment. There has been identified nutritional value of whole-meal pea and soybean flour, additives exceeding the protein content on 13.2–23.6%, oil content on 1.3–21.2%, sugar content on 3.2–9.3%, which is very important in baking. There has been characterized the influence of the type of ingredients (pea, soybean flour) on the rheological properties of dough using farinographic analysis, when 5% addition of pea flour (the variety ‘Flagman 9’) to composite mixtures did not worsen the physical traits of the dough, 10 and 15% addition reduced dough stability on 1–2 minutes, valorimetric assessment on 4–6 e.u., but water absorption capacity of flour raised on 6% in relation to wheat flour. The addition of whole-meal soybeans (the variety ‘Samer 1’) strengthened and improved the physical the dough parameters, however, the volume of bread reduced because of a decrease in gluten percentage in the mixtures and the prevailing salt-soluble (globulins) and water-soluble (albumin) protein fractions. There has been estimated the efficiency of mixtures of premium wheat flour with wholemeal pea and soybean flour, when the overall baking assessment gave positive results of 4.0–4.6 points; in that case the bread is attractive, of regular shape, with smooth crust without cracks, the crumb color is light yellowish with fine porosity, but a little denser than in control, the smell is pleasant and fragrant.